Rare-earth-free noncollinear metallic ferrimagnets Mn4-xZxN with compensation at room temperature. (1st August 2022) - Zhang, Rui; He, Yangkun; Fruchart, Daniel; Coey, J.M.D.; Gercsi, Zsolt
Abstract: Compensated ferrimagnets show no net magnetization like antiferromagnets, but their transport and magneto-optic properties resemble those of ferromagnets, thereby creating opportunities for applications in high-frequency spintronics and low energy loss communications. Here we study the modification of the noncollinear triangular ferrimagnetic spin structure of Mn4 N by a variety of metallic substitutions Z (Z = Cu — Ge and Ag — Sn) to achieve compensation at room temperature. The noncollinear frustrated 2.35µB moments of Mn on 3 c sites of the (111) kagome planes tilt about 20° out-of-plane in Mn4 N and are easily influenced by the substitutions on 1 a sites, leading to an efficiency of compensation in Mn4- x Z x N that increases gradually from group 11 (Cu, Ag) to group 14 (Ge, Sn) with increasing number of valence electrons. Elements from the 5 th period are more efficient for compensation than those from the 4 th period due to lattice expansion. The manganese site moments analyzed by constrained density functional theory are determined by Z, orbital hybridization, charge transfer and the tilt angle. The Ga compound with compensation at room temperature for x ≈ 0.26 is recommended for high-frequency spintronic applications. Graphical abstract: Image, graphical abstract